2012
DOI: 10.1212/wnl.0b013e3182703fbc
|View full text |Cite
|
Sign up to set email alerts
|

Absence of early epileptiform abnormalities predicts lack of seizures on continuous EEG

Abstract: In patients without epileptiform abnormalities during the first 4 hours of recording, no seizures were subsequently detected. Therefore, EEG features early in the recording may indicate a low risk for seizures, and help determine whether extended monitoring is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
72
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 25 publications
8
72
0
1
Order By: Relevance
“…Seizure frequencies in certain patient populations in our study were similar to previous reports: central nervous system infection (30% vs. 25%-33% in the literature) (Claassen et al, 2004;Jordan, 1995;Shafi et al, 2012), postoperative from a neurosurgical procedure (29% vs. 18%-23%) (Claassen et al, 2004;Shafi et al, 2012), hypoxic ischemic encephalopathy (29% vs. 20%-54%) (Claassen et al, 2004;DeLorenzo et al, 1998;Shafi et al, 2012), patients with brain tumor (27% vs. 17%-54%) (Claassen et al, 2004;DeLorenzo et al, 1998;Jordan, 1995;Shafi et al, 2012), epilepsy-related (25% vs. 24%-56%) (Claassen et al, 2004;FIG. 2.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Seizure frequencies in certain patient populations in our study were similar to previous reports: central nervous system infection (30% vs. 25%-33% in the literature) (Claassen et al, 2004;Jordan, 1995;Shafi et al, 2012), postoperative from a neurosurgical procedure (29% vs. 18%-23%) (Claassen et al, 2004;Shafi et al, 2012), hypoxic ischemic encephalopathy (29% vs. 20%-54%) (Claassen et al, 2004;DeLorenzo et al, 1998;Shafi et al, 2012), patients with brain tumor (27% vs. 17%-54%) (Claassen et al, 2004;DeLorenzo et al, 1998;Jordan, 1995;Shafi et al, 2012), epilepsy-related (25% vs. 24%-56%) (Claassen et al, 2004;FIG. 2.…”
Section: Discussionsupporting
confidence: 90%
“…These data suggest that it may not be necessary to perform cEEG monitoring for 24 to 48 hours on patients who have generalized slowing as the only abnormality on the initial 30 minutes of cEEG recording. A recent study by Shafi et al (2012) found similar results in that the lack of epileptiform discharges early in cEEG monitoring (within 4 hours) predicted the absence of seizures on subsequent cEEG monitoring. With the data we present, providers can make an early determination of a patient's seizure risk based on their baseline EEG pattern, rather than waiting to determine when/if the first epileptiform discharge will appear.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations